2015
DOI: 10.21829/myb.2015.210427
|View full text |Cite
|
Sign up to set email alerts
|

Preservación de la madera usando productos naturales

Abstract: It is a current concern in the wood preservation field to avoid the use of toxic chemicals and develop new technologies based on low environmental impact agents and sustainable principles. Under this expectation, an intended state-of-the-art is introduced on the application of natural products such as traditional tar and wood oils as well as tannins and plant extracts. A particular revision to heartwood chemical components is offered. The combined methods of using natural and chemical components are reviewed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
(44 reference statements)
1
15
0
5
Order By: Relevance
“…Nevertheless, linseed oil showed relatively more protective effect against termite on all wood species. Previous studies also showed similar improvement in termite resistance after vacuum pressure oil application of oils (Koski 2008, Unsal et al 2009, Manalo and Acda 2009. Kukui oil improved resistance to Coptotermes formosanus (Nakayama and Osbrink 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, linseed oil showed relatively more protective effect against termite on all wood species. Previous studies also showed similar improvement in termite resistance after vacuum pressure oil application of oils (Koski 2008, Unsal et al 2009, Manalo and Acda 2009. Kukui oil improved resistance to Coptotermes formosanus (Nakayama and Osbrink 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Traditionally, wood protection against fungi, mildew, moulds, or insects has been effectively ensured by impregnation using different natural substances, such as plant oils, tars, and extracts with varying degrees of protection, but until recently they were not sufficiently promoted (González-Laredo et al 2015). Natural products for wood protection purposes include plant and wood extracts, essential oils, waxes and resins from bark, and biopolymers (e.g.…”
Section: Bio-based Coatings For Wood Protection Using Natural Productsmentioning
confidence: 99%
“…The natural durability of wood is usually correlated to its extractives content and composition (Carter et al 1978;Taylor et al 2006;Santana et al 2010;Andrady et al 2015). When a comparison is made between natural extractives compounds from wood and plants and common substances used for wood preservation in terms of effectiveness, the natural ones mentioned are generally favored for safety and have versatile applications, considering both their biocide and antioxidant character, as well as their metal binding ability (Kartal et al 2006;Syofuna et al 2012;González-Laredo et al 2015;Sablik et al 2016). These extractives act by decreasing the hygroscopic character of wood surfaces and thus inhibiting decay activity for a wide range of biological organisms such as human pathogens, insects, or fungi, with a positive impact upon wood durability.…”
Section: Extractives From Wood and Plants With Biocide Propertiesmentioning
confidence: 99%
“…Asimismo, agentes microbianos de control biológico de conocido uso, eficacia y que conforman un paradigma en el control de plagas, tal como Bacillus thuringensis, motiva a conocer el estilo y ciclo de vida de bacterias y otros microrganismos con la finalidad de usarlos en la preservación de la madera. De igual forma, nuevas o novedosas moléculas sintéticas y productos naturales con actividad biológica como controladores de plagas están surgiendo como una solución parcial para el control de organismos deletéreos que dañan la madera (Damian et al, 2010;González-Laredo et al, 2015;Ramírez-López et al, 2016).…”
Section: Natural Compounds With Wood Preserving Potentialunclassified
“…contiene componentes que son eficaces para combatir algunos hongos y termitas xilófagas (Cheng et al, 2006;Tascioglu et al, 2013). Recientemente Singh y Singh (2012) reportaron que sustancias de hojas wood (Damian et al, 2010;González-Laredo et al, 2015;Ramírez-López et al, 2016).…”
Section: Natural Compounds With Wood Preserving Potentialunclassified